2021
DOI: 10.1155/2021/3627878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiarrheal Activity of 80% Methanolic Extract of the Leaves of Cordia africana (Lamiaceae) in Mice

Abstract: Background. Diarrheal disease is a major cause of morbidity and mortality throughout the world, particularly in developing countries. Currently available drugs are linked with adverse effects, contraindications, and risk of resistance. Traditionally, the leaf concoction of Cordia africana is claimed to be used for diarrhea. However, the safety and efficacy of the leaf extract have not been scientifically approved yet. Therefore, the study was conducted to validate its antidiarrheal activity and safety profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…constituents that have pharmacological activities against diarrhea. Moreover, the extracts of Z. officinale (Zhang et al 2020), hydromethanolic extract of C. africana leaves and root bark (Asrie et al 2016, Ferede et al 2021, and methanol bark extracts of H. acida revealed antidiarrheal activities. The literature supports the indigenous knowledge possessed by locals in managing diarrhea in the study area.…”
Section: Preparation and Administration Of Traditional Remediesmentioning
confidence: 97%
“…constituents that have pharmacological activities against diarrhea. Moreover, the extracts of Z. officinale (Zhang et al 2020), hydromethanolic extract of C. africana leaves and root bark (Asrie et al 2016, Ferede et al 2021, and methanol bark extracts of H. acida revealed antidiarrheal activities. The literature supports the indigenous knowledge possessed by locals in managing diarrhea in the study area.…”
Section: Preparation and Administration Of Traditional Remediesmentioning
confidence: 97%
“…Epidemiological studies revealed that diarrhea had been the second cause of death, next to pneumonia, in under-five children globally by 2021 [ 6 ]. Diarrhea-related child death was found at a higher magnitude (78%) in the disadvantaged regions such as African and Southeast Asian [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the several mechanisms to explain the laxative effect of castor oil, one is the inhibition of intestinal Na+/K + -ATPase activity. Thus, reducing normal fluid absorption through activation of adenylate cyclase or mucosal cyclic adenosine monophosphate-mediated active secretion and nitric oxide release [ 23 , 24 ]. Moreover, castor oil promotes smooth muscle contraction via its metabolite, ricinoleic acid.…”
Section: Discussionmentioning
confidence: 99%